STRATEGI GURU PAI DALAM MENINGKATKAN RELEGIUSITAS SISWA DI SDN 08 REJANG LEBONG (PIONIR: JURNAL PENDIDIKAN, 2020)
This study aimed to find out a portrayal of PAI teacher’s strategies in improving students’ religiosity at SDN 08 of Rejang Lebong, Bengkulu. This study applied a qualitative approach, and a PAI teacher and a school principal were engaged as the key informants. Data were gathered using observation and interview techniques, and the data were analyzed using the Miles’ et al theory comprising data reduction, data presentation, and conclusion drawing. This study concluded that PAI teacher’s strategies at SDN 08 of Rejang Lebong in improving students’ religiosity extended to: 1. Convincing their students to things as needed by using the method of giving advice; 2. Giving guidance by encouraging students to understand and practice Islamic teachings properly by applying the methods of exemplification, habituation, punishment, gifts and attention; 3. Encouraging students to understand and practice Faith, Islam, and Ihsan with actualization and application in daily life by implementing the methods of habituation, exemplification, and attention.
Keywords: Strategy; Teacher; Students; Religiosity